The energy content and demographic composition of Antarctic krill (Euphausia superba) swarms in East Antarctica - Cataldo-Mendez, Camila; Kawaguchi, So; Cox, Martin J.; Melvin, Jessica; Rae, Victor; Swadling, Kerrie M. (Frontiers in Marine Science, 2024)
Antarctic krill (Euphausia superba) aggregations are important in the Southern Ocean ecosystem; however, the amount of energy that krill swarms contain is unknown. We assessed the population structure of E. superba swarms in East Antarctica for two different sectors corresponding to the study areas of the ENRICH (2019) and TEMPO (2021) voyages. We also estimated swarm energy content based on calorific values for whole animals and key tissues (gonads, digestive gland, and muscle). A relationship between the energy content of muscle and gonads in gravid and adult females was detected: The higher the energy content in muscle tissue, the lower the energy content in the gonad tissue. This relationship was consistent for different female maturity stages, suggesting a trade-off in energy allocation between somatic growth and reproduction. Females will redirect energy to gonad development at the expense of somatic growth. Total swarm energy was calculated using the volumetric density of each swarm estimated from an acoustic survey. Four swarm types (A-D) were determined based on the body length and maturity stage of the individuals. The highest energy contents were found in Type B swarms, composed predominantly of adult males and females, and Type D swarms, comprising mostly gravid females. Trends in swarm demographic composition and energy content were consistent between surveys. We recommend swarm energy be incorporated into ecosystem models to represent energy transfer to top predators.